Distortion control of thin sections by single-sided laser peening. (April 2019) - Yang, Ruoyu; Hu, Yongxiang; Luo, Mingsheng; Cheng, Han; Yao, Zhenqiang
Highlights: General single-sided laser peening cannot enhance thin sections without distortion. Single-sided laser peening with suitable small spots can cause no distortion. Single-sided laser peening can generate compressive residual stress on both sides. The effect of spot size on distortion behaviors in laser peening has been revealed. Abstract: Thin sections are widely used in industry and need surface hardening to improve their anti-fatigue properties. This study proposes an improved single-sided LP as an effective way for the surface hardening of thin sections with self-occlusion on one side to overcome the difficulty in double-sided LP. Controlled experiments are conducted on a few specimens with thin sections to investigate the distortion behavior after LP treatment with different process parameters. Finite element method is used to analyze the generation of geometry distortion and explain the difference between LP treatment with several process parameters. The results show that both laser intensity and spot size are of great concern in the geometry distortion after single-sided LP, generating different distortion directions. Single-sided LP with a suitable process parameter set of laser intensity and spot size can enhance specimens without distortion. Numerical model shows the generation of different distortion behaviors is highly related to the bending moment, which is calculated from plastic strain field. Besides, part of plastic strain produced by local deformation varies after LP treatment with different spot sizes, which generates different distortion profiles with the same laser intensity. Furthermore, compressive residual stress is induced on both sides of thin sections by single-sided LP treatment, which ensures the effectivity for the treatment of thin sections.